LONG DISTANCE TRAINING SEMARANG RELIGIOUS TRAINING CENTER - Nikmatul Afiyah; Naili Farida; Hardi Warsono; Tri Yuniningsih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Distance training has become a solution for the Semarang Religious Training Center in overcoming budget constraints and improving the competence of state civil servants. This study aims to analyze the implementation of distance learning based on George C. Edward's policy implementation model, which includes four factors: communication, resources, disposition, and bureaucratic structure. The research method used is descriptive qualitative, with data analysis techniques based on interviews, observations, and document studies. The results of the study indicate that the implementation of distance learning at the Semarang Religious Training Center faces various challenges, such as limited human resource competence, lack of supporting facilities (such as soundproof rooms and internet access), and weak commitment of implementers in running the program. In addition, communication between organizers, participants, and teachers is not optimal, even though it has been supported by social media and online learning platforms. In terms of bureaucratic structure, the existing standard operating procedures still need to be improved to support the sustainability of the program more effectively. The conclusion of this study emphasizes the importance of enhancing human resource competence, providing adequate infrastructure, and better coordination between stakeholders to ensure the success of the implementation of distance learning.